Every trainer's handbook - Agochiya, Devendra (Sage Publications, 2002)
This manual is a comprehensive, step-by-step practical approach to planning and delivering a training programme. Important points have been appropriately elaborated and further reinforced through examples. Guidelines are also provided to assist trainers in carrying out specific tasks. An essential tool for training managers, trainers and instructors from both the management and development fields.